microRNAs in the Lymphatic Endothelium: Master Regulators of Lineage Plasticity and Inflammation - Yee, Daniel; Coles, Mark C.; Lagos, Dimitris (Frontiers in Immunology, 2017)
MicroRNAs (miRNAs) are highly conserved, small non-coding RNAs that regulate gene expression at the post-transcriptional level. They have crucial roles in organismal development, homeostasis, and cellular responses to pathological stress. The lymphatic system is a large vascular network that actively regulates the immune response through antigen trafficking, cytokine secretion and inducing peripheral tolerance. Here, we review the role of miRNAs in the lymphatic endothelium with a particular focus on their role in lymphatic endothelial cell (LEC) plasticity, inflammation and regulatory function. We highlight the lineage plasticity of LECs during inflammation and the importance of understanding the regulatory role of microRNAs in these processes. We propose that targeting miRNA expression in lymphatic endothelium can be a novel strategy in treating human pathologies associated with lymphatic dysfunction.